Evaluation of shaping performance and surface changes of two different minimally invasive shaping file systems used in resin blocks - Özata, Merve Yeniçeri; Falakaloğlu, Seda; Eskibağlar, Mehmet (My University, 2023)
Aims: This study aimed to compare the shaping ability of T-endo MIS and TruNatomy (TRN) file systems in J-shaped resin root canals and to investigate the deformation of the files after two acrylic block preparation and two sterilization cycles. Methods: Forty acrylic blocks were numbered, then four file groups (n=10) were established: T-endo MIS glider (15.04) + T-endo MIS Finisher (25.04) (first and second usage) and TRN Glider (17.02) + TRN Prime (26.04) (first and second usage). Preoperative and postoperative images after the root canal preparation of simulated acrylic blocks were taken for each sample, and superimposed. The amount of resin removed from both the inner and outer walls of the canal to the level of 3, 5, and 7 mm from the apical point was measured, and the amount of transportation was calculated. Additionally, the deformation of the files was examined under a scanning electron microscope before and after usage and sterilization process. Results: Tip deformation of TRN files increased with the number of uses (p=0.007). With the second use, the surface deformation of the MIS files increased (p=0.015). There was no difference in cutting-edge deformation in either file type according to the number of uses (p>0.05). There was no difference in transportation values between the MIS and TRN file systems at any level (p>0.05). The file systems did not show a significant difference in the amount of transportation between first and second use (p>0.05). Conclusion: When TRN (26.04) and MIS (25.04) NiTi rotary files were used twice on acrylic blocks, the amount of deformation did not differ. Both file types were similar in terms of transportation values.
Keywords: Acrylic block; canal transportation; file deformation; minimally invasive shaping